Strategi Pengembangan Komoditas Kopi Excelsa Di Kabupaten Jombang Provinsi Jawa Timur - Saifullah, Rikza; Raharja, Sapta; Suharjo, Budi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2021)
Excella coffee is one of the plantation commodities in Jombang Regency which is currently being developed as a leading commodity. This study aims to see the existing condition of the commodity and the appropriate development strategy. The results of the study show that the Location Quotient value of Excella Coffee is 1,62 in 2019 with a potential land of 8.454,32 hectares. The recommended derivative product based on the Analytical Hierachy Process method is ground coffee with a score of 0,541. The Internal Factor Evaluation matrix shows that the main strengths of commodities are distinctive flavors (0.6673) and regional specialties (0,4643). The weakness is the product has not yet known to the market (0,3121). The External Factor Evaluation matrix shows that the opportunities in the form of large market potential (0,7980) and Information Technology Development (0,8937). The existing threat is competition with other regional commodities (0,.4731). The main recomended strategies of SWOT analysis are: accelerating IG certificate (0,135), increasing product promotion (0,122), strengthening quality assistance processes (0,117), and establishing coffee farmer cooperative (0,117).